Two long‐term phase 3 studies of enarodustat (JTZ‐951) in Japanese anemic patients with chronic kidney disease not on dialysis or on maintenance hemodialysis: SYMPHONY ND‐Long and HD‐Long studies. Issue 2 (2nd September 2021) - Akizawa, Tadao; Nangaku, Masaomi; Yamaguchi, Takuhiro; Koretomo, Ryosuke; Maeda, Kazuo; Yamada, Osamu; Hirakata, Hideki
Abstract: Enarodustat (JTZ‐951) is an oral hypoxia‐inducible factor prolyl hydroxylase inhibitor developed for treating anemia in chronic kidney disease. Two open‐label, uncontrolled phase 3 studies evaluated the 52‐week safety and efficacy of enarodustat in Japanese anemic patients with chronic kidney disease not on dialysis ( n = 132) [SYMPHONY ND‐Long study] or on maintenance hemodialysis ( n = 136) [SYMPHONY HD‐Long study]. The most frequent adverse events were viral upper respiratory tract infection (25.8%) followed by chronic kidney disease (8.3%) in the SYMPHONY ND‐Long study, and viral upper respiratory tract infection (49.3%) followed by contusion (16.9%) and diarrhea (16.9%) in the SYMPHONY HD‐Long study. The incidence of any adverse events did not increase over time. Mean hemoglobin levels and 95% confidence intervals were maintained within the target range (10.0–12.0 g/dl) over 52 weeks in both studies. The long‐term safety and efficacy of enarodustat were confirmed in Japanese anemic patients with chronic kidney disease.